Association between predominantly plant-based diets and iron status in Chinese adults: a cross-sectional analysis. Issue 9 (2nd November 2016) - He, Jingjing; Shen, Xin; Fang, Aiping; Song, Jie; Li, He; Guo, Meihan; Li, Keji
Abstract: Current evidence of the relationship between diets and Fe status is mostly derived from studies in developed countries with Western diets, which may not be translatable to Chinese with a predominantly plant-based diet. We extracted data that were nationally sampled from the 2009 wave of China Health and Nutrition Survey; dietary information was collected using 24-h recalls combined with a food inventory for 3 consecutive days. Blood samples were collected to quantify Fe status, and log-ferritin, transferrin receptor and Hb were used as Fe status indicators. In total, 2905 (1360 males and 1545 females) adults aged 18–50 years were included for multiple linear regression and stratified analyses. The rates of Fe deficiency and Fe-deficiency anaemia were 1·6 and 0·7 % for males and 28·4 and 10·7 % for females, respectively. As red meat and haem Fe consumption differed about fifteen to twenty times throughout the five groups, divided by quintiles of animal protein intake per 4·2 MJ/d, only Fe status as indicated by log-ferritin ( P =0·019) and transferrin receptor ( P =0·024) concentrations in males was shown to be higher as intakes of animal foods increased. Log-ferritin was positively associated with intakes of red meat ( B =0·3 %, P =0·01) and haem Fe ( B =12·3 %, P =0·010) in males and with intake of non-haem Fe in females ( B =2·2 %, P =0·024). We conclude that diet has a very limited association with Fe status in Chinese adults consuming a traditional Chinese diet, and a predominantly plant-based diet may not be necessarily responsible for poor Fe status.